“Plan estratégico para el desarrollo turístico cultural en el cantón Riobamba provincia de Chimborazo” - Quiroz Mesa, María Belén (2016)
The design of the Strategic Plan to develop the tourism in the canton Riobamba is sustained in the determination of the cultural problematic and his possible solutions, besides the implementation of strategies that mitigate the existing weaknesses and optimize the strengths with which it counts this territory in the cultural area. The present investigation forms his structure in three relevant directives; the development of a diagnosis that allowed to recognize the strong and weak points of the zone with regard to the cultural aspect, with what it was possible to conclude that the canton Riobamba possesses abundance of cultural attractions of great historical and traditional relevancy that are capable of attracting to great abundance of the tourist local, national market and inclusive internationally. The present investigation forms his structure in three relevant directives; the development of a diagnosis that allowed to recognize the strong and weak points of the zone with regard to the cultural aspect, with what it was possible to conclude that the canton Riobamba possesses abundance of cultural attractions of great historical and traditional relevancy that are capable of attracting to great abundance of the tourist local, national market and inclusive internationally. A market research was executed to obtain important information for the cultural area of the canton by means of the application of 378 surveys directed tourists who visit this zone and 10 interviews to civil servants who work in the National Institute of Riobamba's Cultural Heritage, with what it was possible to denote the great acceptance that they possess with everything related to the tourist cultural offer of the canton Riobamba and in turn, the interest that they express to rest on the implementation of a strategic plan that it allows to strengthen and to develop to the cultural area in this zone of the country Finally there was designed the strategic cultural plan bearing in mind the requirements and the most urgent needs in what concerns the cultural tangible and intangible heritage of this locality, for which constituted the philosophical and strategic frame of the plan by means of the development of the mission, vision and strategic aims; and immediately afterwards there were designed the actions of the strategic plan contained in five projects related to the restoration and revitalization from the cultural heritage, training to actors of the tourist activity, product design and promotion of the cultural offer of the canton.